Sa Ugoy ng Duyan: Mothers Raising a Child with Down Syndrome - Tanganim, Vince; Barrantes, Jamyla Kathleen; Villafranca, Maurice; Cusi, Karen (JPAIR Multidisciplinary Research, 2017)
One of the most prevalent neurodevelopmental disorders in the country is Down syndrome. Raising a child with this disorder is not an easy feat for the parents or caregivers. This descriptive phenomenological study intends to explore the experiences of mothers in Lucena City in raising a child with Down syndrome. Ethical clearance was granted by the ethical review board. Trustworthiness and rigor were also ensured. Data thickness and rich descriptions were achieved through the five (5) participants who were chosen through criterion sampling with the help of key informants from the SPED department. The narratives were gathered through the unstructured interview. Transcribed narratives were analyzed through the use of Collaizi’s (1978) method and result into three (3) themes namely: (1) Pakikipaglaro sa Tadhana: A Pleasant Controversy, (2) Paghehele sa Problema: Guts and Glory and (3) Pag-aakay sa Kinabukasan: Stronger till the end. The outcome unveils the world of these mothers not only with a glimpse of their adversaries but mostly features this as a blessing in disguise. Their child’s condition has helped bring community awareness and perspective on people in the same situation. Their experiences have also inspired other parents who likewise struggle with having a child with different abilities.